Acetaldehyde as a drug of abuse: insight into AM281 administration on operant-conflict paradigm in rats - Plescia, Fulvio; Brancato, Anna; Marino, Rosa Anna Maria; Cannizzaro, Carla (Frontiers in Behavioral Neuroscience, 2013)
Increasing evidence focuses on acetaldehyde (ACD) as the mediator of the rewarding and motivational properties of ethanol. Indeed, ACD stimulates dopamine release in the nucleus accumbens and it is self-administered under different conditions. Besides the dopaminergic transmission, the endocannabinoid system has been reported to play an important role in ethanol central effects, modulating primary alcohol rewarding effect, drug-seeking, and relapse behavior. Drug motivational properties are highlighted in operant paradigms which include response-contingent punishment, a behavioral equivalent of compulsive drug use despite adverse consequences. The aim of this study was thus to characterize ACD motivational and rewarding properties employing an operant-conflict paradigm in which rats, trained to lever press in order to get ACD solution (0.9%), undergo extinction, reinstatement and conflict sessions, according to a modified Geller–Seifter procedure. Furthermore, the role played by CB1 receptor system in modulating ACD-induced effects were investigated through the administration of CB1 receptor antagonist, AM281 (1 mg/kg, i.p.) during the extinction-, relapse-, and conflict-experiments. Our results indicate that ACD is able to induce and maintain an operant behavior, a high number of responses during extinction, an increase in the lever presses during the reinstatement phase, and a higher emission of punished responses during the conflict experiments, when compared to controls. The administration of AM281 is able to decrease ACD-seeking behavior during extinction, the number of lever presses during reinstatement and to strongly decrease the punished responses for ACD. Our data strengthen the idea that ACD may be responsible for the central effects of ethanol, and pinpoint at the CB1 system as one of the neural substrates underlying its addictive properties.